Pengaruh Pengelolaan Uang Saku, Gaya Hidup dan Kontrol Diri Terhadap Perilaku Konsumtif Mahasiswa dengan Literasi Keuangan Sebagai Variabel Moderasi - Sarlince Sandy Mauk; Maximus Leonardo Taolin; Dionisious Alupan (Pusat Riset dan Inovasi Nasional, 2026)
This study examines the consumptive behavior of students in the Management Study Program, Faculty of Economics and Business, Universitas Timor, who are in the transitional phase toward financial independence. The research investigates the effects of pocket money management, lifestyle, and self-control on students’ consumptive behavior, as well as the role of financial literacy as a moderating variable. The study aims to identify causal relationships among variables and develop an empirical model of students’ consumptive behavior. A quantitative approach was employed, using a survey of 287 students selected through purposive sampling, and analyzed with Moderated Regression Analysis (MRA). The results indicate that pocket money management, lifestyle, and self-control have a positive and significant effect on students’ consumptive behavior. Furthermore, financial literacy significantly moderates these relationships, strengthening the effects of pocket money management and self-control, as well as enhancing the influence of lifestyle on consumptive behavior, enabling non-essential consumption to be more planned and controlled. These findings suggest that even students with good financial management and self-control may still engage in consumptive behavior, but it occurs within controlled limits due to financial literacy. The study concludes that financial literacy plays a strategic role in shaping students’ consumption patterns, both as a reinforcement for pocket money management and self-control and as a regulator of lifestyle influence. The findings contribute to the development of an empirical model of students’ consumptive behavior and provide recommendations for educational institutions in designing effective financial literacy programs.